Phenomenon of anisotropy in the group of germanic preterite-present and inchoative verbs as a factor of analytization - Valeria Bondarenko; Andriy Botsman; Olga Dmytruk (Актуальні проблеми української лінгвістики: теорія і практика)
The purpose of this article is to find out the influence of anisotropy on the process of analytization which causes the development of the future tense forms in the Germanic languages.  The analytization of temporal (the future tense in particular) forms is connected with the separation of the initial formant in the analytical morphological temporal forms. The initial formant varies in the East, West, and North Germanic languages performing one and the same function of future time preference. Comparison of different Germanic languages gives the possibility to trace the gradual analytization of verb grammatical forms, and to find out individual group features which are characteristic for preterite-present and inchoative verbs.